Forecasting the mortality rates of Malaysian population using Heligman-Pollard model - Ibrahim R.I.; Mohd R.; Ngataman N.; Abrisam W.N.A.W.M. (American Institute of Physics Inc., 2024)
Indexed by WOS/ Scopus